Not only to create the memory of ourselves as indigenous peoples, but also to teach how to see that memory (2014)
Marisol Calambás Soscué tells us about her creative quest for new techniques and plastic form aiming to express the ancestral memory of the Nasa People to whom she belongs. One should escape from the artificial stagnancy imposed by the touristic market sticking the ‘handicraft’ label upon indigenous crafts and demanding the repetition of so-called ancestral patterns. Marisol tells us that Indigenous creativity is fluid and is constantly transforming the channels for memory communication. It is therefore necessary to educate the public so as they may learn to see their transformations.